Unexpected Exacerbation of Neuroinflammatory Response After a Combined Therapy in Old Parkinsonian Mice - Gil-Martínez, Ana Luisa; Cuenca, Lorena; Estrada, Cristina; Sánchez-Rodrigo, Consuelo; Fernández-Villalba, Emiliano; Herrero, María Trinidad (Frontiers in Cellular Neuroscience, 2018)
The design of therapeutic strategies that focus on the repositioning of anti-inflammatory and antioxidant drugs are a great bet to slow down the progression of neurodegenerative disorders. Despite the fact that Parkinson’s disease (PD) is an age-related pathology, almost all experimental studies are carried out in young animals. Here, we evaluated the possible neuroprotective effect of the combination of the antioxidant N-acetylcysteine (NAC) and the anti-inflammatory HA-1077 in aged 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated mice (C57BL/6 mice, 20 months old), whose individual treatment has been shown to have neuroprotective effects in this Parkinsonism model. Interestingly, NAC+HA-1077-based treatment produced a significant increase in dopaminergic neuronal death accompanied by an increase in microglial and astroglial activation in the Substantia Nigra pars compacta (SNpc) and striatum of old-Parkinsonian mice compared to their control group. Astroglial response was also explored by co-immunostaining for GFAP and S100b together with p-JNK and it was found to be particularly exacerbated in the MPTP+NAC+HA-1077 group. The unexpected toxic effects found in the combined use of NAC and HA-1077 in old-Parkinsonian mice highlight the importance of taking into account that in elderly Parkinsonian patients the combination of some drugs (most of them used for other different age-related alterations) can have side effects that may result in the exacerbation of the neurodegenerative process.